A Review on Relative Factors of Employees Empowerment of SMES (پژوهش‌های مدیریت عمومی, 2012)
SMES plays a vital role in economic and social development of countries. They formed a lot of economical majority in states. it’s no doubt That the human resource is very important in relative case. The aim of this paper is to study and analyze the effect of five empowerment dimintions including meaningfull, effectiveness, competent, trust and self confidence. Sample population was132 of SMES employees in zahedan. data gathered tool was questionnaire and analyzed by freedman regression and SPSS software. The result shows that organizational condition and employees competent are better forecaster factors to empowerment of employees in SMES, and so competent is more empower than other dimensions.